PH-Sensitive nanoparticles based on amphiphilic imidazole/cholesterol modified hydroxyethyl starch for tumor chemotherapy. (1st February 2022) - Xu, Zhilang; Yang, Die; Long, Tao; Yuan, Lun; Qiu, Shi; Li, Defu; Mu, Changdao; Ge, Liming
Abstract: pH-Responsive nanoparticles (NPs) have emerged as an effective antitumor drug delivery system, promoting the drugs accumulation in the tumor and selectively releasing drugs in tumoral acidic microenvironment. Herein, we developed a new amphiphilic modified hydroxyethyl starch (HES) based pH-sensitive nanocarrier of antitumor drug delivery. HES was first modified by hydrophilic imidazole and hydrophobic cholesterol to obtain an amphiphilic polymer (IHC). Then IHC can self-assemble to encapsulate doxorubicin (DOX) and form doxorubicin-loaded nanoparticles (DOX/IHC NPs), which displayed good stability for one week storage and acidic sensitive long-term sustained release of DOX. As a result, cancer cell endocytosed DOX/IHC NPs could continuously release doxorubicin into cytoplasm and nucleus to effectively kill cancer cells. Additionally, DOX/IHC NPs could be effectively enriched in the tumor tissue, showing enhanced tumor growth inhibition effect compared to free doxorubicin. Overall, our amphiphilic modified HES-based NPs possess a great potential as drug delivery system for cancer chemotherapy. Graphical abstract: Unlabelled Image